Investigation and Study of the Twenty-third Maqamat of the Explanation of the Maqamat al-Hariri by al-Jijzi (died after the year 600 AH - MOHAMMED, TAREQ ATIYAH; Buraa, Mohanad Majeed (Journal of Tikrit University for Humanities, 2024)
Maqamat is considered one of the literary arts that became famous in the later eras, which expressed the issues of man and humanity in a philosophical way that provided lessons for learners. It presented treatments of the Arab personality in a sometimes sarcastic manner and at other times in a serious manner, on humanitarian issues. Due to their importance in Arabic literature, many writers and scholars explained these maqamat, with the aim of removing ambiguity and vagueness about them, especially after it became clear to them that one of the goals of creating the maqamat was to teach young people Arabic linguistic vocabulary, but in an indirect way. The maqamat included many linguistic words, especially foreign vocabulary. This explanation of the Maqamat is one of the explanations that have not seen the light yet, and we are in the process of studying and investigating it. It is the explanation of the Maqamat Al-Hariri by Al-Sijzi (died after the year 600 AH). Anyone who follows Al-Sijzi’s personality will find that he was knowledgeable in many fields, but he did not stand out. Because of the loss of many of his works, the names of which we can only find, and because he did not present his opinions on many issues, especially in jurisprudence, and the issues in which there was disagreement. The reason for his lack of fame at that time may be due to the fact that he did not travel to seek knowledge. But his scholarly personality is clear in his explanations of Al-Hariri’s Maqamat. He used to balance the explanations and choose from them what suits the wording that came in Al-Maqamat. He would defend Al-Hariri valiantly, describing Hariri’s critics as ignorant. Our work here in this research was limited to the twenty-third Maqamat, studying and investigating, believing in the importance of reviving the literary heritage. This explanation of Al-Sijzi on Al-Maqamat Al-Hariri is characterized as one of the intermediate explanations, as it is not one of the very lengthy explanations, such as the explanations of Al-Fanjdihi and Al-Sharishi Al-Andalusi, nor one of the very brief explanations that were limited to explaining mysterious, strange, and rare meanings, such as the explanation of Abu Talib Abd Al-Jabbar Al-Maafiri Al-Qurtubi. Some of the commentators chose few words from each maqamat to explain, clarify, and remove ambiguity from them.